Genome-wide investigation of ABCB, PIN, and AUX/LAX gene families and their involvement in the formation of leaf protrusions in Sesamum indicum - Li, Yanli; Ma, Yujia; Gong, Huihui; Cui, Xinxiao; Wang, Xin; Dong, Yuling; Chen, Ying; Zhao, Junsheng (Frontiers in Plant Science, 2025)
Sesamum indicum, a highly esteemed oil crop, has exhibited remarkable value and potential in diverse areas encompassing the economy, food industry, and health. We have observed that there are small protrusions on the leaves of the indehiscent capsule material G1358. No obvious difference was detected on overall auxin content between the leaves of G1358 and LZ1 from metabolomic analysis. However, auxin levels at the base of G1358 leaves were notably higher than in LZ1, suggesting a correlation between the small protrusions at the base and polar auxin transport (PAT). PAT is essential for regulating growth and development across different plant tissues. PAT primarily relies on three families of transporter proteins: ABCB, PIN, and AUX/LAX. However, the ABCB, PIN, and AUX/LAX protein families in Sesamum indicum have not been systematically characterized. Herein, we identified 21 SiABCBs, 11 SiPINs, and 5 SiLAXs in S. indicum. Our analysis indicated that tandem duplications have facilitated the expansion of SiLAX, SiPIN, and SiABCB gene families, which have undergone purifying selection throughout their evolutionary history. Transcriptome screening and RT-qPCR analysis revealed that SiABCB3, SiABCB6, and SiPIN10 positively regulate PAT, whereas SiABCB7 and SiABCB9 negatively regulate PAT in G1358. These regulatory interactions contribute to the formation of small protrusions in G1358 leaves and enhance the rate of photosynthesis. Our findings provide a theoretical foundation for understanding PAT genes and their roles in the environmental adaptation of sesame.